Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae) - Yoshitake, Hiraku (Zootaxa, 2017)
Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 was described based on the female holotype collected from Ilocos Norte, North Luzon, Philippines. Since that time, it has been left unstudied for almost a century until I examined the holotype of M. (O.) orbiferoides in 2010 at Senckenberg Naturhistorische Sammlungen, Museum für Tierkunde, Dresden (SMTD). Recently, Barševskis (2016) described Macrocyrtus imomzodai based on two female specimens from Ilocos Norte, Luzon. Judging from the original description and dorsal and lateral habitus images, it is quite apparent that M. imomzodai is conspecific with M. (O.) orbiferoides. Here I propose a new synonymy based on these examinations. I thank Klaus-Dieter Klass, Olaf Jäger, Christian Schmidt, and Matthias Nuss (SMTD) for their support during my stay in Dresden. My thanks are also due to Steve R. Davis (American Natural History Museum, New York) and Naoko Nakahara (Tsukuba) for their help for preparing the manuscript.